Analysis of The Implementation of Constructivism in Science Education: a Case Study - Amsal Alhayat; Mia Roosmalisa Dewi; Suci Indah Putri (PAEDAGOGIA, 2023)
The values of constructivism in science learning are demonstrated in how students construct their knowledge. However, science learning still needs to implement this learning concept fully. Therefore, this research aims to analyze the presence of constructivism in the implementation of science learning at a Junior High School in Sungai Raya. The study was conducted using a qualitative method. Data collection was done through interviews, observations, and documentation. The data analysis technique used was descriptive analysis. The research results show that constructivism in implementing science learning at a Junior High School in Sungai Raya can be seen in the planning, implementation, and evaluation of learning. Overall, the presence of constructivism is indicated by student involvement, learning model selection, learning strategies, and assessment forms. Although the presence of constructivism in science learning at a Junior High School in Sungai Raya has been identified, there is still a need for improvement in learning support facilities, assessment, and innovative learning approaches to accommodate students' more empirical and contextual learning experiences.